Sentinel Lymph Node Biopsy in T3 and T4b Breast Cancer Patients: Analysis in a Tertiary Cancer Hospital and Systematic Literature Review - De Oliveira-Junior, Idam [UNESP]; Nahas, Eliana Aguiar Petri [UNESP]; Cherem, Ana Cristina; Nahas-Neto, Jorge [UNESP]; Vieira, René Aloisio Da Costa [UNESP] (Karger Publishers, 2020)
Introduction: Breast cancer represents the most common type of cancer among women in the world. The presence and extent of axillary lymph node involvement represent an important prognostic factor. Sentinel lymph node biopsy (SLNB) is currently accepted for T1 and T2 with negative axillae (N0); however, many patients with T3-T4b tumors with N0 are often submitted to unnecessarily axillary lymph node dissection. Materials and Methods: This is a retrospective, observational study of patients treated for breast cancer between 2008 and 2015, with T3/T4b tumors and N0, who underwent SLNB. A systematic review of the literature was also carried out in 5 bases. Results: We analyzed 73 patients, and SLNB was negative for macrometastasis in 60.3% of the cases. With a mean follow-up of 45 months, no ipsilateral axillary local recurrence was observed. In the systematic review, only 7 articles presented data for analysis. Grouping these studies with the present series, the rate of N0 was 32.1% for T3 and 61.0% for T4b; grouping all studies (T3 and T4b n = 431) the rate was 32.5%. Conclusions: SLNB in T3/T4b tumors is a feasible and safe procedure from the oncological point of view, as it has not been associated with ipsilateral axillary relapse.